Students’ Experiences of Online Cooperative Learning for Economics post-Covid-19: A Case of one University in the Eastern Cape Province, South Africa - Qoyi Motsi; Mpiti Pretty Thandiswa; Makena Bulelwa (E-Journal of Humanities, Arts and Social Sciences)
Online Cooperative Learning (OCL) is the learning process in which students learn in small groups using Learning Management Systems (LMSs). OCL flourishes in virtual learning environments that emphasize individual freedom within online learning communities. The purpose of the study was to explore online cooperative learning as a strategy to teach Economics post-COVID-19. The study was guided by May and Dobb’s cooperative learning theory, in which group work is prioritized. The study adopted a qualitative approach underpinned by a case study. A purposive sampling that comprised six instructors and ten students was employed. Data was collected through individual interviews, and it was analyzed using Content Analysis (CA) and categorized using thematic analysis. The findings revealed that students demonstrate academic improvement, flexibility, convenience, and exposure to technological tools. It was concluded that the use of online cooperative learning provides more benefits than setbacks. The study recommended the intensive use of OCL in Economics. Lastly, this study addressed the gap by providing valuable insights into the importance of this instructional approach and enabling instructors to design and implement online cooperative learning experiences that enhance students’ economic literacy and prepare them for real-world economic challenges.